Assessment of Bacterial Communities Associated With the Skin of Costa Rican Amphibians at La Selva Biological Station - Abarca, Juan G.; Vargas, Gabriel; Zuniga, Ibrahim; Whitfield, Steven M.; Woodhams, Douglas C.; Kerby, Jacob; McKenzie, Valerie J.; Murillo-Cruz, Catalina; Pinto-Tomás, Adrián A. (Frontiers in Microbiology, 2018)
Amphibian skin is a suitable environment for rich communities of microorganisms, both beneficial and detrimental to the host. The amphibian cutaneous microbiota has been hypothesized to play an important role as symbionts, protecting their hosts against disease. Costa Rica has one of the most diverse assemblages of amphibians in the world and we know very little about the microbiota of these tropical animals. For comparison with other studies, we explore the diversity of the skin bacterial communities employing16S rRNA amplicon sequencing of swab samples from twelve species of frogs at La Selva Biological Station in Sarapiquí, Heredia province. The predominant phylum detected in our studies was Proteobacteria, followed by Bacteroidetes and Actinobacteria, with these three phyla representing 89.9% of the total bacterial taxa. At the family level, Sphingobacteriaceae and Comamonadaceae were highly represented among samples. Our results suggest that host species and host family are significant predictors of the variation in microbiota composition. This study helps set the foundation for future research about microbiota composition and resilience to unfavorable conditions, leading to improvement in managing strategies for endangered amphibian species.